Beyond individual and group differences : human individuality, scientific psychology, and William Stern's critical personalism - Lamiell, James T. (Sage Publications, 2003)
The author provides book-length treatment of the concept of human individuality in 20th century scientific psychology highlighting the historical contributions made by the German psychologist and philosopher William Stern (1871-1938).